2021
DOI: 10.1051/0004-6361/202141540
|View full text |Cite
|
Sign up to set email alerts
|

Deep Chandra observations of merging galaxy cluster ZwCl 2341+0000

Abstract: Context. Knowledge of X-ray shock and radio relic connection in merging galaxy clusters has been greatly extended in terms of both observation and theory over the last decade. ZwCl 2341+0000 is a double-relic merging galaxy cluster; previous studies have shown that half of the southern relic is associated with an X-ray surface brightness discontinuity, while the other half not. The discontinuity was believed to be a shock front. Therefore, it is a mysterious case of an only partial shock-relic connection. Aims… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The southern relic shows few patches of polarized emission with < p >= 13 ± 2 %. Projection effects are likely to play an important role in the depolarization of these relics, as suggested by the disturbed X-ray morphology of the cluster (Zhang et al 2021), merger components along the line-of-sight (Golovich et al 2019b) and high σ RM value (i.e., 35 rad m −2 in the source restframe).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The southern relic shows few patches of polarized emission with < p >= 13 ± 2 %. Projection effects are likely to play an important role in the depolarization of these relics, as suggested by the disturbed X-ray morphology of the cluster (Zhang et al 2021), merger components along the line-of-sight (Golovich et al 2019b) and high σ RM value (i.e., 35 rad m −2 in the source restframe).…”
Section: Discussionmentioning
confidence: 99%
“…Several optical studies of this system (Boschin et al 2013;Benson et al 2017;Golovich et al 2019b) found that it is composed of at least three sub-clusters: two of them are aligned along the NW-SE elongation of the X-ray emission and their merger is possibly responsible for the radio relics formation, while the third one in the north-east is likely to be involved in a secondary merger along the line-of-sight. Zhang et al (2021) performed a detailed analysis of a deep 206.5 ks Chandra observation of ZwCl2341. They discovered the presence of numerous substructures within this cluster and confirmed its complex dynamical state.…”
Section: Abell 3365mentioning
confidence: 99%
See 2 more Smart Citations
“…Several optical studies of this system (Boschin et al 2013;Benson et al 2017;Golovich et al 2019b) found that it is composed of at least three subclusters: two of them are aligned along the northwest-southeast elongation of the Xray emission and their merger is possibly responsible for the radio relics' formation, while the third one in the northeast is likely to be involved in a secondary merger along the line of sight. Zhang et al (2021) performed a detailed analysis of a deep 206.5 ks Chandra observation of ZwCl2341. They discovered the presence of numerous substructures within this cluster and confirmed its complex dynamical state.…”
Section: Introductionmentioning
confidence: 99%